2021
DOI: 10.1002/ps.6344
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in the lethal effects of insecticides against the diamondback moth, Plutella xylostella (L.)

Abstract: BACKGROUND: The diamondback moth, Plutella xylostella (L.), is one of the most destructive pests owing to the rapid development of resistance to various groups of insecticides. Although the rotation strategy has become common, resistance management continues to be a critical issue. RESULTS: In Japan, historical changes in the susceptibility of P. xylostella to insecticides were estimated using 82 references. The meta-analysis using generalized linear mixed models suggested that each mode of action (MoA) had di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…It is possible that nontarget Lepidopterans could also develop resistance to permethrin. Resistance development in pest Lepidopteran species has been reported (Jia et al 2009 ; Grigg-McGuffin et al 2015 ; Uesugi 2020 ; Sun et al 2022 ) and has been reported in a nontarget aquatic invertebrate (Major et al 2022 ). The common aspect of this resistance development is that it occurs in organisms either targeted by the applications or are unintentionally routinely exposed to the insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that nontarget Lepidopterans could also develop resistance to permethrin. Resistance development in pest Lepidopteran species has been reported (Jia et al 2009 ; Grigg-McGuffin et al 2015 ; Uesugi 2020 ; Sun et al 2022 ) and has been reported in a nontarget aquatic invertebrate (Major et al 2022 ). The common aspect of this resistance development is that it occurs in organisms either targeted by the applications or are unintentionally routinely exposed to the insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, Japanese farmers have used the rotation of pesticides with varied modes of action for resistance management. Nonetheless, this technique produces variations in their mortalities ( Uesugi, 2021 ) (IRAC 2019). Fitness costs related to using insecticides could be a possible reason for this disparity, resulting in varying susceptibility against the different modes of action affecting resistance stability ( Jouzani et al, 2017 ).…”
Section: Lepidopteramentioning
confidence: 99%
“…Fitness costs related to using insecticides could be a possible reason for this disparity, resulting in varying susceptibility against the different modes of action affecting resistance stability ( Jouzani et al, 2017 ). Bt, spinosyns, pyridalyl, and aver-mectins/milbemycins may become key components of the rotation approach because their high fitness costs lead to steady and high susceptibility ( Jouzani et al, 2017 ; Yin et al, 2019 ; Uesugi, 2021 ; Kumar et al, 2022 ).…”
Section: Lepidopteramentioning
confidence: 99%
“…The challenge of managing this moth is exacerbated by its strong reproductive potential, rapid generation turnover, protracted growing period, and extensive migration range [3]. The rapid evolution of drug resistance owing to the irrational use of insecticides has made its control a major concern for many countries, yet there is a dearth of effective agrochemicals on the market to combat it [4,5]. It has been found that the moth is highly resistant to organophosphorus, carbamates, pyrethroids, novel chemical insecticides, and toxins from Bacillus thuringiensis at the present time [1,6,7].…”
Section: Introductionmentioning
confidence: 99%